MANAJEMEN STRES PADA PEMILIK USAHA KECIL MENENGAH (UKM) BIDANG KULINER DI KOTA KEDIRI - Hallie J. Sahertian; Felik S. W.W. Broto; Gunawan, Frans Christian (Universitas Katolik Widya Karya Malang, 2020)
Stress management is a common knowledge and should beapplied by each individual in order to reduce high stress levelsdue the demands and pressures of works and personal life ofeach individual. Although not most of all, Stress Managementcan be implemented by a business owner (SMEs) so that anyactivity which they do business to run well and thrive. Causesof stress on business owners came from a variety of sourceswhich is derived from organizational factors and individualfactors that each individual has a different and its own way ofdealing with every obstacle that can possibly create stress.The purpose of this study was to determine the causes ofstress on business owners, especially in culinary’s bussinesowners (Food and Beverage) and how they perform is seen bythe Stress Management Organizational and Individualaspects. The subjects in this study is the Owner of Small andMedium Enterprises (SMEs) in Culinary derived from Kediribe a participant in this study. The approach used in this studyis a qualitative case study approach. From the results of thestudy, researchers found that the phenomena that occurrelated to the causes of stress and stress management isdifferent for each individuals. The Stressors on Owner ofSmall and Medium Enterprises (SMEs) in Culinary are need toknown that the process of Stres Manajement can be done inorder to maintain the continuity of their bussiness.